Prosthetic management of dentigerous cyst associated with impacted mandibular molar - Shanmuganathan Natarajan; Athiban Inbarajan; Madhan Seenivasan; Fathima R Banu; T T Saravanan; Prathiba Saran (Wolters Kluwer Medknow Publications, 2018)
Dentigerous cysts are benign odontogenic cysts occurring from the dental follicle of an unerupted or developing tooth. This cyst is usually asymptomatic but has the potential to attain a large size and become aggressive. These lesions are usually associated with the impacted third molars and canines. The treatment for this cyst is the extraction of the impacted tooth and enucleation of the cyst. A prosthodontist should be involved in the restoration of the lost structure from the point of diagnosis to establish proper function and improve the quality of life for the patient. We present a case report of a dentigerous cyst associated with an impacted mandibular molar which was surgically removed, and the defect was closed by an obturator fabricated before the surgical procedure.